Okullarda yaşanan siyasi ayrımcılığın bireysel ve örgütsel etkileri - Kara, Sultan Bilge Keskinkılıç (Kastamonu Üniversitesi, 2016)
Siyasi ayrımcılık, bireylerin işyerlerinde, sahip oldukları siyasi görüş nedeniyle maruz kaldıkları, adil olmayan tutum ve davranışlardır. Siyasi ayrımcılık okullarda örgütsel alanda yaşanan ve üzerinde çok fazla çalışılmayan sorunlardan biridir. Bu çalışmanın amacı, eğitim kurumlarında öğretmenlerin maruz kaldıkları siyasi ayrımcılığın bireysel ve örgütsel etkilerini belirlemektir. Araştırmada olgubilim deseni kullanılmıştır. Araştırmanın çalışma grubunu çalıştığı kurumda siyasi ayrımcılığa maruz kaldığını belirten 12 öğretmen oluşturmaktadır. Veriler araştırmacı tarafından hazırlanmış olan görüşme formu yardımıyla yüz yüze görüşmeler yapılarak toplanmıştır. Araştırmada siyasi ayrımcılığa uğrayan öğretmenlerin en fazla maruz kaldıkları ayrımcı davranışların özlük haklarının kullanımının engellenmesi, ders dışı etkinliklerin yapılmasının engellenmesi ve fazla iş yükü verilmesi olduğu; ayrımcı davranışlar karşısında öğretmenlerin yoğunluklu olarak nefret, öfke ve mutsuzluk duygusu yaşadıkları, ayrımcı davranışların öğretmenler üzerinde bireysel ve örgütsel etkilerinin olduğu sonucuna ulaşılmıştır

Discrimination is one of the most important problems that employees encounter in workplace and it stems from the prejudices that are manifested as a result of different treatment of the employees with the same knowledge, skills and performance. The aim of the study is to determine the effects of political orientation discrimination on both individual teachers and organizations. The study employed a phenomenologic research design. The sample consists of 12 teachers who stated that they were exposed to political orientation discrimination in their workplaces. The study found the following as the most common discriminations that teachers are exposed to: restraining the use of their personal rights, restraining the teachers from carrying out extracurricular activities, and assigning too much workload to teachers. It was also found that when teachers are exposed to such discriminations, they become hateful, angry and unhappy. Furthermore, discriminatory behaviors also have some individual and organizational effects on teachers. The most common individual effect was found to be distancing from those with different political affiliations and attachment to those with the same political affiliations. The organizational effects of discrimination were found to be the loss of motivation for work and attachment to the institution.
Individual and organizational effects of political orientation discrimination on teachers in schools
Keywords: Siyasi ayrımcılık; Ayrımcılığın etkileri; Political orientation discrimination; Effects of discrimination